2008
DOI: 10.1021/ol801971t
|View full text |Cite
|
Sign up to set email alerts
|

L-Selectride-Mediated Highly Diastereoselective Asymmetric Reductive Aldol Reaction: Access to an Important Subunit for Bioactive Molecules

Abstract: L-Selectride reduction of a chiral or achiral enone followed by reaction of the resulting enolate with optically active α-alkoxy aldehydes proceeded with excellent diastereoselectivity. The resulting α,α-dimethyl-β-hydroxy ketones are inherent to a variety of biologically active natural products.Asymmetric aldol reactions leading to the stereocontrolled generation of β-hydroxy carbonyl derivatives are among the most important reactions in organic synthesis. 1 Consequently, a number of effective methodologies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Reaction with chiral isopropylidenebutyraldehyde however, provided a 1:1 mixture of diastereomers. The corresponding reaction with isovaleraldehyde provided a 1:1 mixture of diastereomers 210 , suggesting that the α-chirality of the isopropylidene- d -glyceraldehyde is responsible for the diastereoselectivity as proposed in the stereochemical model 208 116. Indeed, reaction with an achiral enone 211 and isopropylidene- d -glyceraldehyde provided single isomer 212 .…”
Section: Asymmetric Reductive Aldol Reactionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reaction with chiral isopropylidenebutyraldehyde however, provided a 1:1 mixture of diastereomers. The corresponding reaction with isovaleraldehyde provided a 1:1 mixture of diastereomers 210 , suggesting that the α-chirality of the isopropylidene- d -glyceraldehyde is responsible for the diastereoselectivity as proposed in the stereochemical model 208 116. Indeed, reaction with an achiral enone 211 and isopropylidene- d -glyceraldehyde provided single isomer 212 .…”
Section: Asymmetric Reductive Aldol Reactionmentioning
confidence: 94%
“…Recently, we have developed a highly diastereoselective asymmetric reductive aldol reaction 116. As shown in Figure 44, aldol reaction of the enolate generated by addition of l -selectride to enone 207 and isopropylidene- d -glyceraldehyde in ether at −78 °C provided only one single diastereomer 209 , in 70% yield.…”
Section: Asymmetric Reductive Aldol Reactionmentioning
confidence: 99%
“…Our exploration of this reductive aldol strategy showed that several representative aldol adducts can be prepared in good yield and high diastereoselectivity when the reactant aldehyde contains an α-chiral center. 4 The synthesis of peloruside A was carried out by removal of the p -methoxybenzyl protecting group and oxidation of the primary alcohol to the corresponding acid, followed by Yamaguchi lactonization to provide macrolactone 69 . This was then converted into (+)-peluroside A.…”
Section: Peloruside Amentioning
confidence: 99%
“…3 We will also describe a recent asymmetric reductive aldol process developed in our laboratory in the context of the synthesis of peloruside A, a potent anticancer agent with clinical potential. 4,5 Furthermore, we report an asymmetric aldol-based synthesis of a stereochemically defined bis-tetrahydrofuran (bis-THF) scaffold present in ginkolide natural products. 6 This scaffold has been successfully incorporated in the design and development of Darunavir, a HIV-1 protease inhibitor for the treatment of multi-drug-resistant HIV-1 variants that has recently been approved by the US Food and Drug Administration (FDA).…”
mentioning
confidence: 99%
“…In fact, b-hydroxy ketones can serve as versatile building block for the asymmetric synthesis of carbohydrates, amino acids and many other biomolecules (4)(5)(6). They also provide privileged structural functionalities that exist in many important natural products (7)(8)(9)(10)(11)(12). For example, the b-hydroxy ketones functionalities exist in macrolide classes of antibiotics such as telithromycin and cethromycin which are targeted primarily against Gram-positive bacterial strains including Streptococcus pneumoniae and S. pyogenes, fastidious Gram-negative strains including Haemophilus influenzae and Moraxella catarrhalis, atypicals Mycoplasma pneumoniae, Chlamydia pneumoniae and Legionella pneumophilia (13).…”
mentioning
confidence: 99%